The Known Unknowns: An Enigmatic Pathway of C17-Polyacetylenic Oxylipins in Carrot (Daucus carota L.) - Abdul Wakeel Umar; Hamad Hussain; Naveed Ahmad (Current Issues in Molecular Biology, 2025)
C17-polyacetylenic (PA) oxylipins are bioactive compounds in carrots (Daucus carota L.) with structurally unique features and diverse biological roles. These PA-derived compounds have garnered attention for their potential contributions to human health, particularly in cancer prevention and anti-inflammatory applications. This trade-off between health benefits and sensory quality underscores the importance of understanding the genetic and biochemical basis of PA biosynthesis, as it may allow for the development of carrots with optimized levels of these compounds that balance both nutritional and sensory qualities. In this review, we seek biochemically inspired strategies to elucidate the complexities of PA-derived oxylipins biosynthesis in carrots, a topic that remains largely unexplored. By integrating current knowledge on polyacetylene biology, biosynthesis, genetic and enzymatic factors involved in their production and the implications for enhancing the medicinal value of carrots we aim to provide a foundation for future research that could unlock the full potential of carrots as a source of health-promoting bioactive compounds.